Stabilizing Cationic Palladium Single-Atom Sites on Heteroatom-Doped Carbon for Selective Hydrogen Peroxide Electrosynthesis - Fortunato, Guilherme V.; Gunnarson, Alexander; Hosseini, Hannaneh; You, Xiangyu; Bhuyan, Pallabi; Choi, Ji Sik; Jeon, Hyo Sang; Zhao, Xingshen; Lourenco, Julio C.; Lim, Sumin; Wang, Huize; Buzanich, Ana Guilherme; et al. (John Wiley & Sons Ltd., 2026)
Single-atom catalysts (SACs) offer significant potential for the sustainable electrosynthesis of hydrogen peroxide (H2O2) via the two-electron oxygen reduction reaction (2e- ORR). However, their practical deployment is hindered by challenges related to limited operational stability and intricate synthetic procedures. Here, a family of cationic Pd single-atom complexes anchored on nitrogen-, sulfur-, and dual N,S-doped hollow carbon spheres (HCS) is reported, prepared via mild vapor-phase doping combined with wet impregnation of Pd(acac)2. Systematic tuning of the heteroatom environment enables precise control over the Pd electronic state and local coordination, enhancing selectivity and long-term stability under acidic, peroxide-rich conditions. Operando ICP-MS and advanced spectroscopy reveal that sulfur-doping induces favorable charge redistribution, reinforcing Pd-support interactions and suppressing demetallation, while nitrogen doping enhances ORR activity. Notably, dual N,S-co-doping achieves a synergistic balance between catalytic performance and stability. This strategy offers a rational design framework for robust ligand-containing SACs, advancing sustainable electrocatalytic technologies well beyond H2O2 synthesis.